Un/Commoning Pedagogies: Moving To/Gather in Difference - Dasha A. Chapman; Dellecave, J; Jones, Adanna Kai; Kivenko, Sharon Freda; LaMothe, Mario; Weidman, Lailye; Zabriskie , Queen Meccasia (Radical Teacher, 2023)
The Un/Commoning Pedagogies Collective is a cohort of educators committed to centering embodiment in our social justice education work. As seven dancer-scholars, variably positioned, and differentially located within the academy, we bring movement-based pedagogies into our teaching across the intersections of diverse fields—Anthropology, Sociology, African American and Africana Studies, Gender, Sexuality and Women’s Studies, Dance, and Performance Studies. Here, we offer a glimpse into our concerns, commitments, and experiences and invite you to join us in this process. We write from the urgent need to craft spaces for co-creating knowledge through body-based, intersectional anti-racist methods that move with, rather than negate, difference, and together as authors share strategies and methods for cultivating such opportunities, as well as our own experiences of doing so from our divergent positionalities.